2021
DOI: 10.1038/s41598-021-01617-4
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue after acquired brain injury impacts health-related quality of life: an exploratory cohort study

Abstract: This study aimed to identify the consequences of fatigue, fatigability, cognitive and executive functioning, and emotional state on health-related quality of life (HRQoL) in a clinical group of outpatients after acquired brain injury (ABI). This cross-sectional retrospective study included assessing outpatients at a rehabilitation clinic with WAIS-III working memory and coding subtests, and self-rating scales (Fatigue Impact Scale, Dysexecutive Questionnaire, Hospital Anxiety and Depression Scale, and the dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…Furthermore, mental fatigue was associated with deficits in episodic memory and executive functions. This is in agreement with some earlier acquired brain injury studies [ 41 , 42 ]. Unlike hypertension, diabetes was significantly related to cognitive performance, which is consistent with a growing body of evidence indicating that diabetes impairs cognition over and above the burden of cerebrovascular pathology [ 43 ].…”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, mental fatigue was associated with deficits in episodic memory and executive functions. This is in agreement with some earlier acquired brain injury studies [ 41 , 42 ]. Unlike hypertension, diabetes was significantly related to cognitive performance, which is consistent with a growing body of evidence indicating that diabetes impairs cognition over and above the burden of cerebrovascular pathology [ 43 ].…”
Section: Discussionsupporting
confidence: 94%
“…Therefore, it is possible that improvements in self-care are measured across both the MPAI-4 and the FIM + FAM. Fatigue is a common sequelae of ABI and has been associated with impaired executive functioning and quality of life [ 42 ]. These findings indicate that improvements in fatigue over time are associated with the capacity to make greater gains in both motor and cognitive function throughout neurorehabilitation, suggesting that improvements in fatigue may be associated with both alleviated cognitive dysfunction and reduced physical disability.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies show CF to have a negative impact on HRQOL in multiple patient populations [ 48 , 49 , 50 , 51 ], and also, in subgroups of CCS, it was already suggested that (chronic) fatigue affects HRQOL [ 15 , 17 ]. The current study confirms this, showing the impact of CF on a broad range of HRQOL subscales in a generalizable cohort of CCS.…”
Section: Discussionmentioning
confidence: 99%